A Gene Regulatory Network-Inspired Self-Organizing Control for Wireless Sensor Networks. (26th August 2015) - Byun, Heejung; Park, Jaesung
Biologically inspired modeling techniques have received considerable attention for the realization of robustness, scalability, and adaptability with simple local interactions and limited information. Gene Regulatory Networks (GRNs) play a central role in understanding natural evolution and development of biological organisms from cells. In this paper, we employ GRN principles and propose a new GRN model for self-organizing control of Wireless Sensor Networks (WSNs) with dual aims of energy saving and delay guarantee. Through this scheme, each sensor node schedules its state autonomously according to the controlled gene expression and protein concentration of the proposed GRN model. Simulation results also indicate that the proposed scheme achieves good performance in meeting delay requirements and conserving energy in WSN systems.